(untitled) (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2025)
This article examines the representation of the double through the Nordic folkloric theme of changelings in the Icelandic series Katla (2021). The research objectives are three: (1) To understand Katla’s narrative and aesthetic complexity, particularly in its transitions between Nordic noir and post-Nordic Noir; (2) To explore how Icelandic cultural context, specifically the geomythology of volcanism, shapes narrative development; and (3) To analyze the main character, Gríma, as an illustration of the double through changelings, aiming to understand her narrative characterization, existential constitution, etiological affiliations, and ontological relationships. The methodology involves authors associated with narratological studies and theoretical frameworks related to studies of the double, alongside a priori categories within an interdisciplinary framework encompassing literature, psychoanalysis, and philosophy. Ultimately, it is concluded that the desire to reclaim a past emotional life and the experience of loss, which act as the driving force behind illusion in the character and its changeling’s dramatic arc, shape the figure of the double within the work.